Navigating uncertainty: exploring parents' knowledge of concussion management and neuropsychological baseline testing - Matthew Hagopian; Michael P. Jorgensen; Hugo Lehmann; Fergal O'Hagan (Frontiers Media S.A., 2024)
IntroductionParents play an important role in preventing and managing sport-related concussions among youth sport participants. Research indicates that parents understand the severity and consequences associated with the injury but gaps exist in their knowledge of its management. Neuropsychological baseline testing (NBT) is a modality that has gained interest in youth sport to purportedly better manage concussion injuries. Little is known about parents' perspectives on the use of NBT in the management process.MethodsThe present qualitative study used Protection Motivation Theory as a guiding framework and employed focus groups (N = 2) with parents (N = 11) to gain insight into parents' perceptions and experiences with concussion management, specifically focusing on NBT.ResultsInductive Content Analysis developed a core theme of navigating uncertainty. Participants expressed uncertainty about the nature of concussion and its management process, where concussion was not always easy to identify, youth were not always reliable reporters, and there was no prescribed or proscribed path for recovery. Personal experience and concussion management policy provided participants with a degree of certainty in managing concussions. Participants gave NBT mixed reviews in potentially promoting greater certainty but also held reservations about its usefulness in concussion management.DiscussionWe discuss findings relative to existing knowledge and theory in youth sport concussion and identify implications for practice.